Effect of Electroacupuncture on Key Muscles on Motor Function Recovery of Lower Limbs in Patients with Incomplete Spinal Cord Injury - Wen GUO; Jun LENG; Fangyue WEI; Huimin LIU; Meng TIAN; Chen ZHANG; Xiaolei FANG (康复学报)
Objective:To observe the effects of electroacupuncture on key muscles on motor function of lower limb in patients with incomplete spinal cord injury.Methods:A total of sixty patients with incomplete spinal cord injury were divided into control group and treatment group of 30 cases respectively according to the random number table method. The control group was treated with conventional rehabilitation; on the basis of this, the treatment group was treated with electroacupuncture on key muscles, and different acupuncture points were selected for treatment of key muscles of lower limbs according to different dysfunctions of the patients, once a day, five times a week, a total of 6 weeks'treatment. Patients were assessed with American Spinal Injury Association (ASIA) lower extremity exercise score (LEMS), modified Barthel index (MBI) score, and modified Ashworth scale (MAS) before and after 6 weeks'treatment, respectively. The two groups were compared in terms of limb motor function, spasm level, and daily living ability, the improvement situation.Results:There was no significant difference in LEMS, MBI and MAS before treatment between the two groups (P> 0.05). After 6 weeks'treatment, the indicators of the two groups were compared with those before treatment, and the improvement was statistically significant (P< 0.05). At the end of treatment, the LEMS, MBI and MAS scores of the treatment group were (8.87±1.36), (19.33±6.12) and (1.40±0.56), which were better than those of the control group (6.13±1.31), (15.00±6.43) and (0.97±0.61), and the differences were statistically significant (P< 0.05). It showed that motor function, spasm level and daily life activity ability of the two groups were improved after treatment, and the improvement degree in the treatment group was significantly better than that in the control group.Conclusion:The electroacupuncture on key muscles combined with rehabilitation training is effective in improving motor function of lower limb and self-care ability in patients with incomplete spinal cord injury. It is of great significance for the patient's lower limb muscle strength recovery and early restoration of walking function.